2015
DOI: 10.1038/srep14134
|View full text |Cite
|
Sign up to set email alerts
|

A novel natural product inspired scaffold with robust neurotrophic, neurogenic and neuroprotective action

Abstract: In search for drugs to treat neuropsychiatric disorders wherein neurotrophic and neurogenic properties are affected, two neurotrophically active small molecules specially crafted following natural product leads based on 2-oxa-spiro[5.5]-undecane scaffold, have been thoroughly evaluated for their neurotrophic, neurogenic and neuroprotective potential in ex vivo primary culture and in vivo zebrafish and mouse models. The outcome of in vivo investigations suggest that one of these molecules is more neurotrophic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 26 publications
4
35
0
Order By: Relevance
“…Neurotrophic factor-mediated TrkB signaling is important for the regulation of proliferation and enhanced neurogenesis of embryonic precursors, and for the maintenance of survival of neuronal populations 48 , 49 . TrkB signaling induces the production of the transcription factor, CREB, through the activation of protein kinase cascades; BDNF or NT4 expression coupled with CREB phosphorylation is thought to be one of the key modulatory mechanisms underlying neurogenesis 50 52 . We found that mBMSC and EA, especially EA, could influence the expression of neurotrophic factors such as BDNF and NT4, in turn stimulating the transactivation of CREB.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophic factor-mediated TrkB signaling is important for the regulation of proliferation and enhanced neurogenesis of embryonic precursors, and for the maintenance of survival of neuronal populations 48 , 49 . TrkB signaling induces the production of the transcription factor, CREB, through the activation of protein kinase cascades; BDNF or NT4 expression coupled with CREB phosphorylation is thought to be one of the key modulatory mechanisms underlying neurogenesis 50 52 . We found that mBMSC and EA, especially EA, could influence the expression of neurotrophic factors such as BDNF and NT4, in turn stimulating the transactivation of CREB.…”
Section: Discussionmentioning
confidence: 99%
“…From the neurotrophin or neurotrophic factor family, BDNF has been shown to play a critical role in maintaining proper neural functions. 38 , 41 , 42 An attenuation in its level in brain circuitry is observed in animal models of neuropsychiatric disorders, including depression, anxiety, and related mood disorders. 43 45 The treatment of animal models with antidepressants and anxiolytics has been shown to increase its level in the affected circuitry.…”
Section: Resultsmentioning
confidence: 99%
“… 13 15 In this direction, we and others have focused on the exploration of novel small molecules based on diverse natural product scaffolds and their simplified analogues for neuroactive functions. 16 , 17 This study is based on our effort in evaluating fellutamide B synthetic path intermediates for their in vitro and in vivo neuroactive properties.…”
Section: Introductionmentioning
confidence: 99%
“…Golgi Cox staining was carried out on brain sections of 100 μm thickness using a previous protocol ( Chakravarty et al, 2015 ). A total of six each of unstressed wild-type and Wdr13 -/0 mice, and, five wild-type and six Wdr13 -/0 socially isolated mice were studied.…”
Section: Methodsmentioning
confidence: 99%